2p-2(6-2p)=2(p-5)-2

Simple and best practice solution for 2p-2(6-2p)=2(p-5)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2p-2(6-2p)=2(p-5)-2 equation:


Simplifying
2p + -2(6 + -2p) = 2(p + -5) + -2
2p + (6 * -2 + -2p * -2) = 2(p + -5) + -2
2p + (-12 + 4p) = 2(p + -5) + -2

Reorder the terms:
-12 + 2p + 4p = 2(p + -5) + -2

Combine like terms: 2p + 4p = 6p
-12 + 6p = 2(p + -5) + -2

Reorder the terms:
-12 + 6p = 2(-5 + p) + -2
-12 + 6p = (-5 * 2 + p * 2) + -2
-12 + 6p = (-10 + 2p) + -2

Reorder the terms:
-12 + 6p = -10 + -2 + 2p

Combine like terms: -10 + -2 = -12
-12 + 6p = -12 + 2p

Add '12' to each side of the equation.
-12 + 12 + 6p = -12 + 12 + 2p

Combine like terms: -12 + 12 = 0
0 + 6p = -12 + 12 + 2p
6p = -12 + 12 + 2p

Combine like terms: -12 + 12 = 0
6p = 0 + 2p
6p = 2p

Solving
6p = 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
6p + -2p = 2p + -2p

Combine like terms: 6p + -2p = 4p
4p = 2p + -2p

Combine like terms: 2p + -2p = 0
4p = 0

Divide each side by '4'.
p = 0

Simplifying
p = 0

See similar equations:

| -3n-16=7(n+2) | | -3(4x-15)-8(3x-5)= | | 5d-2-d= | | -4y-8y=-15 | | 9x=9x+18 | | 9y=-1 | | 35+8r=7(2r-1) | | 5x-6=5x-x | | 6-x=-24 | | 3w-5-19w^2+17= | | 8(v+1)-4v=2(2v+2)-8 | | -5(1-5x)=-8x-5 | | 3+25+15x=58 | | 8y+4-6y=7+y-6 | | 2.4p-5=9.4 | | -6v-5(v+5)=-6v-5 | | 6-3x=5x-10x+4+2 | | 23=x^2+7 | | 13x+8x=3x-2 | | 8n+48=48+8n | | 6x+6=p | | -38-8n=-8(n+6)+2n | | y(5y^2+9)-2(7y-6y^3)= | | .2c+.286=2-.143c | | -6+2a=-6(a+5) | | -3(8x-27)-2(x+19)= | | -32+3r=7-4(7r+2) | | q-15=20 | | 4n-(3n+6)=-1 | | 16-a=-4(6a+1)+3a | | 21x-2=18x+30 | | -7(7+5b)=23+b |

Equations solver categories